Low-Cost Synthesis of Zsm-5 Zeolite Using Organic Silica from Rice Husk Agro Waste - Priyadi Priyadi; Nurleni Kurniawati; Vera Prawestiana (UNIVED Press, Dehasen University Bengkulu, 2022)
Rice husk is an agricultural waste that has the potential source of silica in low-cost zeolite synthesis. The objectives of this study were 1) silica extraction of rice husks as synthetic zeolite raw materials, 2) synthesis and characterized ZSM-5 zeolite from rice husks silica. Silica extraction was carried out by soaking rice husks using a heated 15% NaOH solution. Furthermore, 10% HNO3 solution was added to pH 7 for 12 hours. The filtrate dried in an oven for 12 hours at 100oC. Analysis of silica composition using XRF, crystallinity using XRD, and SEM for morphology. The results showed that rice husks were successfully extracted with an alkali addition and used as a source of silica in the synthesized of ZSM-5 zeolite. The zeolite synthesis was carried out with a low temperature of 90oC and a structural directing agent decrease. Zeolite ZSM-5 showed that the level of crystallinity and morphology by the standard ZSM-5 zeolite. Decreasing of the structural directing agent was found at the SDA/Si ratio of 0.045.